Diminished serum repetin levels in patients with schizophrenia and bipolar disorder - Wang, Shuai; Ren, Huixun; Xu, Jie; Yu, Yanjun; Han, Shuiping; Qiao, Hui; Cheng, Shaoli; Xu, Chang; An, Shucheng; Ju, Bomiao; Yu, Chengyuan; Wang, Chanyuan; et al. (Scientific reports, 2015)
Repetin (RPTN) protein is a member of S100 family and is known to be expressed in the normal epidermis. Here we show that RPTN is ubiquitously expressed in both mouse and human brain, with relatively high levels in choroid plexus, hippocampus and prefrontal cortex. To investigate the expression of RPTN in neuropsychiatric disorders, we determined serum levels of RPTN in patients with schizophrenia (n = 88) or bipolar disorder (n = 34) and in chronic psychostimulant users (n = 91). We also studied its expression in a mouse model of chronic unpredictable mild stress (CUMS). The results showed that serum RPTN levels were significantly diminished in patients with schizophrenia and bipolar disorder or in psychostimulant users, compared with healthy subjects (n = 115) or age-matched controls (n = 92) (p < 0.0001). In CUMS mice, RPTN expression in hippocampus and prefrontal cortex was reduced with progression of the CUMS procedure; the serum RPTN level remained unchanged. Since CUMS is a model for depression and methamphetamine (METH) abuse induced psychosis recapitulates many of the psychotic symptoms of schizophrenia, the results from this study may imply that RPTN plays a potential role in emotional and cognitive processing; its decrease in serum may indicate its involvement in the pathogenesis of schizophrenia and bipolar disorder.